Antianemic Activity of Coconut (Cocos nucifera) Haustorium Waste Filtrate in Mice Induced by Sodium Nitrite - Pradawahyuningtyas, Adzimahtinur; Priastomo, Mukti; Rijai, Laode (Ad-Dawaa’ Journal of Pharmaceutical Sciences, 2020)
This study aims to determine the antianemic activity of coconut haustorium (Cocos nucifera) waste against mice induced by sodium nitrite orally for 43 days. The condition of anemia was determined by calculating the hemoglobin level using the Point of Care Test (POCT) method with the easytouch® GCHb and the resulting Hb level was 7.96 ± 0.05 g/dL. After the anemia condition is achieved, the test treatment is given for 21 days by dividing the mice into four groups, each consisting of three mice. The blank group (I) was administered distilled water, the control group (II) was administered Inbion® supplements at a dose of 0.65 mg/20 g BW, groups III and IV were administered coconut haustorium filtrate at a dose of 5 and 15 g/kg, respectively. Then measured the hemoglobin level and the number of erythrocytes. Based on the results of the study, the average hemoglobin levels of the blank, control, I and II groups were 13,9; 15,4; 16,0; and 16.8 g / dL, respectively. The number of erythrocytes during anemia was 1,750,000 / mm3 and after giving coconut kentos was 8,260,000 / mm3. From this study it can be concluded that the highest anti-anemia activity showed by coconut haustorium waste filtrate at dose 15 g/kgBW and had a significant difference in hemoglobin levels (p <0.05) with the blank group.